MENGEMBANGKAN KONSEP DIRI MELALUI KEGIATAN BERMAIN PERAN (PENELITIAN TINDAKAN DI TK B LABSCHOOL STAI BANI SALEH, BEKASI) - Yuli Pujianti (Al Hanin, 2022)
AbstrackThe objective of study was to analyze and describe about the application of role play activity for developing of children self concept. This research was carried out at TK Labschool STAI Bani Saleh for student 5-6 years old in group B. This self concept is needed for early chilhood in order to have understanding about them self.The method employed in this research was Action Research which developed by Kemmis and Taggart. This research action consist of two cycles, every cycle has 4 time action. For every cycle consist of planning, action, monitoring and reflection. The subject of this research were the kindergarten students of group B strawberry class were eleven students. at TK Labschool STAI Bani Saleh. The analysis of data in this research employed by quantitative data and qualitative data. The quantitative data analysis obtained there was a development enhanchment of self concept student from pra intervensi up to second cycle, about 25.5 %. This result was exceeded of the agreement between researcher and collaborator as big as 20%. Depend on that enhancment percentage, the action hypotheses can be accepted. For the analysis qualitative data was employed by analysts interactik model of Miles and Hiberman by the steps: 1. reduction, 2. display. 3. verification by data analyzing from the observasion script, documentation script and interview script during the research. Result of this research show that role play activity was succeeded to develop self concept/br student in group B at T K Labschool STAI Bani Saleh. Â Keyword: selfconcept, role play activity, and action research.